2023
DOI: 10.1002/ece3.10134
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution and phylogenomic analysis of complete chloroplast genomes of Cotinus (Anacardiaceae)

Abstract: Mill. is an oligo-specific genus in the family Anacardiaceae with great ornamental value. It exhibits a disjunct distribution in the Northern Hemisphere particularly in southern Europe, eastern Asia, and North America (Matić et al., 2016;Pell et al., 2011). The common name for Cotinus, "smoketree or smokebush", refers to its unique large panicles, covered with tiny, persistent feathery plumes that give the inflorescences a wispy smoke-like appearance. In addition, owing to their fast growth and drought toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
0
0
0
Order By: Relevance
“…Such expansions and contractions in the IR region across most species manifest as minor deviations in the IR/SC boundary within a few xed genes, which may lead to pseudogenization of certain genes. The examination of the chloroplast genome of B. latifolia and the Anacardiaceae family in this study aligns with prior reports in angiosperms (Liu et al, 2023, Wang et al, 2020, Xin et al, 2023. Typically, the LSC/IRb boundary is situated on or near rps19, rpl2, or rpl22, while IRb/SSC is generally positioned on ycf1 or between ycf1 and ndhF.…”
Section: Adaptive Evolution Analysessupporting
confidence: 88%
See 1 more Smart Citation
“…Such expansions and contractions in the IR region across most species manifest as minor deviations in the IR/SC boundary within a few xed genes, which may lead to pseudogenization of certain genes. The examination of the chloroplast genome of B. latifolia and the Anacardiaceae family in this study aligns with prior reports in angiosperms (Liu et al, 2023, Wang et al, 2020, Xin et al, 2023. Typically, the LSC/IRb boundary is situated on or near rps19, rpl2, or rpl22, while IRb/SSC is generally positioned on ycf1 or between ycf1 and ndhF.…”
Section: Adaptive Evolution Analysessupporting
confidence: 88%
“…The genome lengths of these species ranged from 159,485 to 162,509 bp, with a maximum difference of 3,024 bp. The overall GC content is comparable to that of other species in the Anacardiaceae family, such as Rhus chinensis (37.79%), Pistacia weinmannifolia (37.84%), Toxicodendron vernici uum (37.96%), and Cotinus species (37.9%-38.1%)(Wang et al, 2020, Zheng et al, 2018, Liu et al, 2023…”
mentioning
confidence: 55%
“…Additionally, we found that rpoC2, rbcL and matK also possessed relatively high positive selection sites (8, 8, 7, respectively). Current studies have revealed that these four genes with positive selection in land plants may be very common [31,[35][36][37][38]. For examples, rpoC2 and rbcL have been reported as positive selection in orchid species [31]; matK and rbcL have been identified under positive selection in Ulmaceae species [35]; rpoC2 and clpP have been identified under positive selection in Anisodus species [36]; matK has been identified under positive selection in the Cotinus species [37], and clpP has been identified under positive selection in the Astragalus species [38].…”
Section: Positive Selection and Phylogenetic Analysis Within Zingiber...mentioning
confidence: 99%
“…Current studies have revealed that these four genes with positive selection in land plants may be very common [31,[35][36][37][38]. For examples, rpoC2 and rbcL have been reported as positive selection in orchid species [31]; matK and rbcL have been identified under positive selection in Ulmaceae species [35]; rpoC2 and clpP have been identified under positive selection in Anisodus species [36]; matK has been identified under positive selection in the Cotinus species [37], and clpP has been identified under positive selection in the Astragalus species [38]. The high positive selection sites of clpP, rpoC2, rbcL and matK indicated that these four genes were valuable markers for the adaptive evolution studies of Zingiberales.…”
Section: Positive Selection and Phylogenetic Analysis Within Zingiber...mentioning
confidence: 99%